Methylation status regulates lipoprotein lipase expression in chronic lymphocytic leukemia - Abreu, Cecilia (2013)
Among different prognostic factors in chronic lymphocytic leukemia (CLL), we previously demonstrated that lipoprotein lipase (LPL) is associated with an unmutated immunoglobulin profile and clinical poor outcome. Despite the usefulness of LPL for CLL prognosis, its functional role and the molecular mechanism regulating its expression are still open questions. Interaction of CLL B-cells with the tissue microenvironment favors disease progression by promoting malignant B-cell growth. Since tissue methylation can be altered by environmental factors, we investigated the methylation status of the LPL gene and the possibility that overexpression could be associated with microenvironment signals. Our results show that a demethylated state of the LPL gene is responsible for its anomalous expression in unmutated CLL cases and that this expression is dependent on microenvironment signals. Overall, this work proposes that an epigenetic mechanism, triggered by the microenvironment, regulates LPL expression in CLL disease.